Consistent Analyst Expectation Error and Earnings Management: Evidence from China. Issue 9 (1st September 2016) - Zhou, Zhengyi; Wu, Chongfeng
ABSTRACT: Using data from the Chinese A-share market in 2004–12, we show how cognitive bias of individual analysts led to counterproductive effect in less-developed financial markets. We form an ex ante measure of analysts' expectation error, a measure suitable for markets with a short history. We find that star analysts tend to be more optimistic than ordinary analysts, and their biased opinions influence other analysts because of analyst herding behavior. Two-stage least square regression results suggest that consistent expectation errors among analysts can lead to earnings management. These insights are valuable to investors and regulators.